Adaptive Strategies of Pesantren in Java During COVID-19: Insights into Educational Resilience and Crisis Management - Sabarudin, Sabarudin; Mubin, Muhammad Nurul; Asror, Ahmad Maulana; Nurcendani , Riska Wahyu (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Purpose – This study investigates the adaptive strategies employed by pesantren (Islamic boarding schools) in Java, Indonesia, during the COVID-19 pandemic. It aims to understand how these institutions maintained educational standards amidst the crisis, providing insights that could benefit similar educational systems worldwide. Design/methods/approach – A qualitative multi-case study design was used, focusing on three pesantren: Pesantren Ibnul Qoyyim Yogyakarta, Pesantren Zhilalul Qur'an Jepara, and Pesantren Putri Al-Mawaddah Ponorogo. Data collection methods included direct observations, in-depth interviews, and document analysis. Participants included heads, administrators, and teachers from each pesantren. Data were analyzed using interactive techniques involving open coding, axial coding, and comparative analysis to identify key themes. Findings – The study revealed distinct adaptive strategies across the pesantren: 1) Pesantren Ibnul Qoyyim adopted remote learning via Zoom and implemented stringent health protocols upon students' gradual return. 2) Pesantren Zhilalul Qur'an focused on online Quran memorization and established a dedicated clinic for health monitoring. 3) Pesantren Putri Al-Mawaddah limited external interactions and used a rotating teacher system to maintain educational delivery. Research implications – The findings highlight the resilience and adaptability of pesantren in crises, offering a model for other educational institutions. The study underscores the importance of innovation, flexibility, and cross-sector collaboration in managing educational continuity during global crises. These insights can inform policymakers and educational stakeholders in developing robust crisis management strategies.